Evaluation of Diuron Tolerance and Biotransformation by Fungi from a Sugar Cane Plantation Sandy-Loam Soil - Perissini-Lopes, Bruna [UNESP]; Egea, Tassia Chiachio [UNESP]; Monteiro, Diego Alves [UNESP]; Vici, Ana Claudia; Humberto Da Silva, Danilo Griinig [UNESP]; Oliveira Lisboa, Daniela Correa de [UNESP]; Almeida, Eduardo Alves de [UNESP]; Parsons, John Robert; Da Silva, Roberto [UNESP]; Gomes, Eleni [UNESP] (Amer Chemical Soc, 2016)
Microorganisms capable of degrading herbicides are essential to minimize the amount of chemical compounds that may leach into other environments. This work aimed to study the potential of sandy-loam soil fungi to tolerate the herbicide Herburon (50% diuron) and to degrade the active ingredient diuron. Verticillium sp. F04, Trichoderma virens F28, and Cunninghamella elegans B06 showed the highest growth in the presence of the herbicide. The evaluation of biotransformation showed that Aspergillus brasiliensis G08, Aspergillus sp. G25, and Cunninghamella elegans B06 had the greatest potential to degrade diuron. Statistical analysis demonstrated that glucose positively influences the potential of the microorganism to degrade diuron, indicating a cometabolic process. Due to metabolites founded by diuron biotransformation, it is indicated that the fungi are relevant in reducing the herbicide concentration in runoff, minimizing the environmental impact on surrounding ecosystems.
Keywords: soil fungi; biotransformation; diuron; Plackett-Burman; central composite rotational design; HPLC; LC/MS/MS